Unregulated emissions and health risk potential from biodiesel (KB5, KB20) and methanol blend (M5) fuelled transportation diesel engines. (December 2016) - Agarwal, Avinash Kumar; Chandra Shukla, Pravesh; Patel, Chetankumar; Gupta, Jai Gopal; Sharma, Nikhil; Prasad, Rajesh Kumar; Agarwal, Rashmi A.
Abstract: Diesel engine emissions consist of several harmful gaseous species, some of which are regulated by stringent emission norms, while many others are not. These unregulated emission species are responsible for adverse environmental impact and serious health hazards upon prolonged exposure. In this study, a four-cylinder, 1.4  l, compression ignition (CI) engine was used for characterization of unregulated gaseous exhaust emissions measured at 2500 rpm at varying engine loads (0, 25, 50, 75 and 100%). The test fuels investigated were Karanja biodiesel blended with diesel (KB5, KB20), methanol blended with diesel (M5) and baseline mineral diesel. Fourier transform infrared (FTIR) emission analyzer was used to measure unregulated emission species and raw exhaust gas emission analyzer was used to measure regulated emission species in exhaust. Results show an increasing trend for some of the unregulated species from blends of biodiesel such as formaldehyde, acetaldehyde, ethanol, n- butane however methane reduced upon using these oxygenated fuel blends except methanol, compared to baseline mineral diesel. Nevertheless, no significant changes were observed for sulfur dioxide, iso -butane, n -octane, n -pentane, formic acid, benzene, acetylene and ethylene upon using biodiesel and methanol blends. Graphical abstract: Highlights: Study of unregulated emissions from KB5, KB20 and M5 in a CI engine. Biodiesel blends resulted in significant reduction of CH4 emission. n-C4 H10, HCHO, CH3 CHO, C2 H5 OH emissions decreased with increasing load. CH4, n-C5 H12 and C2 H2 emissions increased with increasing load. Fraction of unidentified hydrocarbons increased at full load.